2004
DOI: 10.1002/sim.2072
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the cross‐over design: an empirical estimation

Abstract: The aim of the present study is to estimate the relative efficiency of cross-over clinical trials as compared to the corresponding parallel designs. A MEDLINE 'full text' search covering years 2000-2003 over the word 'cross-over' identified 40 true cross-over studies with the parametric approach published in leading medical journals. A parallel design is expected to need, in order to achieve the same power, between 4 and 10 times more subjects than the corresponding cross-over design, meaning that cost of a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 52 publications
0
27
0
1
Order By: Relevance
“…Hence good sensitivity of a model is obtained by combining a pain mechanism potently affected by opioids (large effect size or signal), and using a pain assessment that is reliable producing data with modest variance (noise). In general parallel studies give a weaker statistical power than a cross-over design, demanding larger sample sizes [127]. Furthermore, pain measures that only have a small dynamic range allow only a limited sensitivity for detecting analgesic effects.…”
Section: Methodology and Trial Designmentioning
confidence: 99%
“…Hence good sensitivity of a model is obtained by combining a pain mechanism potently affected by opioids (large effect size or signal), and using a pain assessment that is reliable producing data with modest variance (noise). In general parallel studies give a weaker statistical power than a cross-over design, demanding larger sample sizes [127]. Furthermore, pain measures that only have a small dynamic range allow only a limited sensitivity for detecting analgesic effects.…”
Section: Methodology and Trial Designmentioning
confidence: 99%
“…In general, parallel studies give a weaker statistical power than a cross-over design, demanding larger sample sizes. [15] In case of cross-over designed studies, it is important that the investigator is the same in all pain assessments, since gender and appearance of the investigator can influence the pain rating of the volunteers. [16]…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of several conditions, such as Alzheimer's disease, hypercholesteremia, hypertension, and asthma where a body of cross-over studies may exist [9,11,17,20,21]. Here, considering the trials as a group might provide information about carry-over that could be useful either in interpreting existing studies, or planning new studies.…”
Section: Introductionmentioning
confidence: 96%
“…p¡0:05). For example, Garcia and colleagues [9] recently reported that only 45 per cent of cross-over studies published in leading medical journals between 2000 and 2003 provided estimates for the e ect size and its standard error. Additionally we can combine information from di erent types of studies using the information in the p-values.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation